PENGARUH DISIPLIN BELAJAR DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR SISWA KELAS X DI SMK UNGGUL SAKTI KOTA JAMBI - Redi Indra Yudha (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2018)
The purpose of this research is to know the influence of interest in learning, emotional intelligence to the result of learning of class X students at SMK Unggul Sakti Kota Jambi. The population in the study amounted to 130 students. Based on the results of research, it can be concluded that with the discipline in learning and ability in developing or develop the emotional intelligence owned by each student then it will eventually be able to create a strategy in self-management better than ever in following the learning process held.